Reforma dedovanja v Republiki Sloveniji - Žnidaršič Skubic, Viktorija (Podjetje in delo, 2025)
In the article, the author discusses the issue of the planned inheritance reform in the Republic of Slovenia, focusing primarily on the issue of intestate (statutory) inheritance and, within the framework of the latter, the issue of compulsory succession. She concludes that in the area of inheritance, Slovenia has so far not followed the reform trends around the world, nor the needs that Slovenian social reality has been demonstrating for some time. She believes that it will be necessary to change and modernize both the system of intestate (statutory) inheritance and compulsory succession, which otherwise represents a special form of statutory inheritance, although it occurs in cases of testamentary inheritance. Statutory inheritance will need to be reformed primarily in terms of changing the inheritance shares within an individual inheritance order and in doing so, taking into account to a greater extent the legitimate interests of spouses compared to descendants (horizontal protection of heirs). In the case of compulsory succession, it will be necessary to narrow the circle of beneficiaries of the compulsory share, perhaps also change the size of the compulsory shares themselves. The author is reserved when it comes to proposals to change the legal nature of the compulsory share, advising consideration of all arguments for and against such a solution. At the end of the article, the author presents examples of several other areas that would need to be reformed and gives her suggestions on an appropriate way of conducting the reform of inheritance law in general.
Keywords: Dedovanje in nasledstvo; Zakonska reforma